PERJANJIAN ALLAH DENGAN NUH, ABRAHAM, MUSA, DAN DAUD SERTA IMPLIKASINYA BAGI PENDIDIKAN AGAMA KRISTEN - Suryani Lillin; Masjelita (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This study aims to analyze the development of the concept of God's covenant in the Old Testament through four main characters, namely Noah, Abraham, Moses, and David, and examine its implications for Christian Religious Education. The problem that underlies this research is the gap between the theological understanding of the covenant as the basis of the relationship between God and humanity and the practice of Christian Religious Education which still tends to be shallow and merely an exchange of obligations. The method used is a literature study with a theological-historical approach and text interpretation. The results of the study show that (1) God's covenant developed gradually from a comprehensive nature that encompasses all creatures to the formation of a specific faith group, but with the ultimate goal of reaching all nations, and (2) the covenant has profound teaching implications for Christian Religious Education, including the dimensions of character formation, discipleship in the church, and social change rooted in God's faithfulness. This study provides a new contribution by combining covenant theology and contemporary Christian faith education methods in one integrated framework.